Kajian pendahuluan analisis peramalan thunderstorm untuk penyusunan indeks dasar adaptasi kegiatan pertambakan (Suatu tinjauan meteorologi di Jakarta) - Yopi Ilhamsyah (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. A meteorological prespective to analyze the Thunderstorm forecasting in Jakarta has been done. The principal indices to be adapted in a fishpond were also arranged in the study. Storms in Jakarta, so-called as Ordinary Cell Thunderstorms, are frequently arose in the afternoon, particularly during transition period on March-May and September-November in which many of them are triggered by different in surface heating. The latter emerged to an atmospheric instability and force the air parcel to rise through the atmosphere. RAOB was employed to the forecasting of Thunderstorm. A number of such indices as K and Showalter indices as well as CAPE are produced and applied to forecast the conditional instability of the troposphere. The result showed that the extension of inversion layer in 500–300 hPa implied the shrink of humidity and might strength the convective instability. In addition, the higher amount of CAPE proved the maximum velocity of updraft which lead to a strong convection and vertical wind shear during Thunderstorm in Jakarta. On the other hand, based on the storm indices, three principal indices adapted in a fishpond were also arranged i.e. normal, moderate and risk condition.Keywords. Thunderstorm, Storm indices, Fishpond adaption